Ancient Greek history and contemporary social science - Canevaro, Mirko; Erskine, Andrew; Gray, Benjamin D. (Benjamin David), 1983-; Ober, Josiah (Edinburgh Leventis studies ;, 2018)
There is a long history of successful engagement between social science and classical studies. This new collection of essays surveys the current state of the new field of social science Greek history' and demonstrates the potential of this interdisciplinary field.